2014
DOI: 10.1007/s12031-014-0344-1
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Running Wheel Improves Cognitive Functions of Mouse Associated with miRNA Expressional Alteration in Hippocampus Following Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is an insult to the brain that results in impairments of cognitive and physical functioning. Both of human research and animal studies demonstrate that spontaneous exercise can facilitate neuronal plasticity and improve cognitive function in normal or TBI rodent models. However, the possible mechanisms underlying are still not well known. We postulated that spontaneous running wheel (RW) altered microRNA (miRNA) expressions in hippocampus of mice following TBI, which might be assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 27 publications
1
30
0
Order By: Relevance
“…1a). In agreement with the array data described before (Bao et al 2014), miR21 level significantly elevated in hippocampus of TBI-non-runners, compared with that of sham ones (p<0.05). This expressional increase of miR21 in hippocampal was reversed in TBI-runners (p<0.05) but did not reached the level of sham group.…”
Section: Alterations Of Mir21 Levels In Tbi Mice With Rw Exercisesupporting
confidence: 91%
See 3 more Smart Citations
“…1a). In agreement with the array data described before (Bao et al 2014), miR21 level significantly elevated in hippocampus of TBI-non-runners, compared with that of sham ones (p<0.05). This expressional increase of miR21 in hippocampal was reversed in TBI-runners (p<0.05) but did not reached the level of sham group.…”
Section: Alterations Of Mir21 Levels In Tbi Mice With Rw Exercisesupporting
confidence: 91%
“…In the present study, we investigated the effect of RW exercise on spatial learning and memory in relation to miR21 expression using a mouse model of TBI. Since we noted previously that miR21 is up-regulated in hippocampus by TBI (Bao et al 2014), we analyzed hippocampal expression of miR21 after TBI by in situ hybridization. Present evidences showed that mouse miR21 was expressed in the process, cytoplasm and nucleus of hippocampal neuron, and the elevated expression induced by TBI were reversed in the group treated with RW exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts at amelioration have usually focused on environmental manipulations. Examples of these would include the traditional ‘enriched environment’ [5] and the opportunity for exercise on running wheels [6]. With rare exceptions (see Discussion), deep brain stimulation (DBS) has not been tried with the intention of improving behavioral arousal in the manner that is currently being attempted with human patients [7].…”
Section: Introductionmentioning
confidence: 99%